Evaluation of the WPA2-PSK wireless network security protocol using the Linset and Aircrack-ng tools - Acosta-López, Alberto; Melo-Monroy, Elver Yesid; Linares-Murcia, Pablo Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Due to the emergence of new techniques and technologies of intrusion, the wireless network protocols have become obsolete; for this reason, this research seeks to violate and evaluate the security of the WPA2 protocol that is widely used by the Colombian service providers. The first section of this paper introduces the WPA2 protocol by describing its operation and the potential attacks it may suffer; the second part details the methodology used to collect the tests data and to carry out the evaluation necessary for the preparation of this article. In addition, we present the Linset and Aircrack-ng tools for auditing wireless networks that were selected to assess the security of the protocol. Finally, we show the results and conclusions.